Analisis kandungan teaflavin dan tearubigin pada teh hitam yang diolah melalui metode pelayuan kimia bertahap - Shabri Shabri; Dr. Dadan Rohdiana; Hilman Maulana; Sugeng Haryanto; Muhammad Iqbal Prawira-Atmaja (Jurnal Penelitian Teh dan Kina, 2018)
The instability of tea shoots supply from the plantation to the factory was often a problem. In the flush season where tea shoots are abundant, an overcapacity often leads to the uncontrollable withering process. This problem was the cause of the decreased quality of black tea. Theaflavin (TF) and Thearubigin (TR) were chemical substances that positively correlated to the black tea quality. This research conducted to characterize TF and TR quality in two-stages chemical withering. This research treatment consists of two treatments, namely treatment A (plus season), treatment B (minus season), and one control/routine production (treatment C). Treatment A and B used 25 kg of fresh tea shoots to be withered, the first stage was to wither the leaves until it reached 60%, 65%, and 70% of water content. The second stage was to blended those leaves at the first stage and withered it until it reached about 54-56%. For treatment A and B, the enzymatic oxidation (fermentation) time used 90 minutes. Treatment C used 25 kg of fresh tea shot that processed as normal routine production of black tea orthodox-rotor vane process, with enzymatic oxidation time 110 minutes. Every treatment was repeated 3 times. Treatment A produced TF of 0,97% d.b and TR of 15,39 d.b. (ratio 1:15,97). And treatment C produced TF of 0,92% d.b and TR of 13,69% d.b. (ratio 1:14,82). It was concluded that two-stage chemical withering was able to maintain the chemical and organoleptic qualities of black tea.